Do takeover threats stifle or promote managerial efforts to innovate? Evidence from takeover vulnerability, and text-based measure of innovation - Nattarinee Denlertchaikul; Pattanaporn Chatjuthamard; Pornsit Jiraporn; Piyachart Phiromswad (Administrative Sciences, 2022)
Although the role of managers is crucial in shaping firm innovation, it also poses a dilemma. Because innovation is a complicated and long-term process that requires effort and attention, managers may reduce effort in innovation when faced with high takeover threat. This study examines the effects of hostile takeover threats on managerial efforts to innovate. Our results show that more active hostile takeover markets stifle managerial efforts in corporate innovation. The findings suggest that managers tend to be more myopic when firms are exposed to hostile takeover threats. Managers will put less effort into innovation to counter the risk of being dismissed as the expected payoff from such investment is long-term and highly uncertain. Additional robustness checks confirm the results, including random-effects regressions, an alternative measure of innovation, and two instrumental-variable analyses.
Keywords: 350; innovation; managerial myopia; market for corporate control; takeover; takeover threats